An Upper Cretaceous ammonite and inoceramids from the Honna Formation, Queen Charlotte Islands, British Columbia - Riccardi, Alberto Carlos (1981)
The lower part of the Honna Formation contains the Turonian bivalve species Mytiloidea labiatus (Schlotheim) and Inoceramus sppppp. cf. I. multiformis Pergament, whereas its uppermost beds have yielded the presumably Santonian ammonite Plexiotexanites? sp. indet. Therefore the formation appears to range from the early Toronian to the Santonian. The presence of Mytiloides labiatus s.i. in the upper part of the underlying Haida Formation suggests the absence of a prolonged hiatus between the two formations and confirms their partial interfingering.